Research on optimization techniques applied to precision agricultural processes supported by technology in Latin America: Opportunities and a route to follow - Brenes Carranza, José Antonio (2021)
The agricultural sector is facing significant challenges. Producing more food while consuming fewer resources like water, fertilizers, and arable land is probably the most important. Today more than ever, farmers need specialized technological tools to achieve this goal. It is possible to improve agricultural processes by practicing technology-supported precision agriculture. However, more technology development to optimize crop yield is needed worldwide. In this research, we conducted a systematic literature review in which we studied different articles that propose optimization for agricultural processes. We identified some proposals made from multiple researchers at distinct latitudes, focused on optimizing the irrigation and management of pests and diseases. Nevertheless, there are only a few studies that focus on optimizing the crop yield. They do that by controlling the different factors that can affect it. We also found out that only a few studies have been conducted in the Latin American region. Thus, these findings show areas in which there is still a lot of opportunities to contribute to the agro sector in Latin American countries.